Pengaruh Persediaan Bahan Baku Dan Kapasitas Mesin Terhadap Volume Produksi Di Pabrik Temulawak : Studi Kasus Pada PT Bintang Mas Di Tasikmalaya - Tommy Ariestia Suhendra Tee; Rita Tri Yusnita; Suci Putri Lestari (Master Manajemen, 2023)
The objective of this study was for determine and analyze the effect of the amount of raw material inventory and engine capacity simultaneously to volume production at PT Bintang Mas. The sample of this research is company data on the number of inventories of raw materials, machine capacity and production volume in 2018-2020 at PT Bintang Mas. The collection of data through observation. The data used in this research is secondary data in the form of a company's internal data PT Bintang Mas, Based on the results of multiple regression analysis and hypothesis testing by using test of F can be seen that simultaneously the number of inventories of raw materials) and engine capacity significantly affects the volume of production. While based on the hypothesis test by using test t count that the partial amount of raw material inventory there is a significant effect on the volume of production and the capacity of the machine partially significant effect on the volume of production.